The Bhagavata Purana: Selected Readings, by Ravi M. Gupta and Kenneth R. Valpey - Uskokov, Aleksandar (Religions of South Asia, 2019)
The Bhagavata Purana: Selected Readings, by Ravi M. Gupta and Kenneth R. Valpey. New York: Columbia University Press, 2016. xx + 303 pp., 105/£81 (hb), 35/£27 (pb), 34.99/£27 (ebook). ISBN 978-0-23116-900-4 (hb), 978-0-23116-901-1 (pb), 978-0-23154-234-0 (ebook).